An object oriented Python cookbook in quantum information theory and quantum computing - Ramkarthik, M. S.; Barkataki, Pranay (Boca Raton : CRC Press, 2023)
"This first of a kind textbook provides computational tools in state of the art OOPs Python that are fundamental to quantum information, quantum computing, linear algebra and one dimensional spin half condensed matter systems. Over 104 subroutines are included, and the codes are aided by mathematical comments suitably to enhance clarity. Suitable for beginner and advanced readers alike, students and researchers will find this textbook to be a helpful guide and a compendium which they can readily use. Key Features: Includes over 104 codes in OOPs python, all of which can be used either as a standalone program or integrated with any other main program without any issues. Every parameter in the input, output and execution has been provided while keeping both beginner and advanced users in mind. The output of every program is explained thoroughly with detailed examples. A detailed mathematical commenting is done along side the code which enhances clarity about the flow and working of the code"--
Introduction to Python and object oriented programming -- Basic quantum mathematics tools -- Numerical linear algebra operations -- Quantum information and quantum computation tools -- Quantification of quantum entanglement -- One-dimensional quantum spin-1/2 chain models -- Generating random matrices and random vectors.
OCLC-licensed vendor bibliographic record.
Keywords: Quantum theory -- Mathematics -- Data processing; Quantum computing; Python (Computer program language); Object-oriented programming (Computer science); SCIENCE / Quantum Theory